2015
DOI: 10.1111/zsc.12115
|View full text |Cite
|
Sign up to set email alerts
|

A sisters’ story: comparative phylogeography and taxonomy of Hierophis viridiflavus and H. gemonensis (Serpentes, Colubridae)

Abstract: We used a multidisciplinary approach to infer the taxonomy and historical biogeography of Hierophis viridiflavus and H. gemonensis, performing molecular analyses of itochondrial (16S, Cyt-b, ND4) and nuclear markers (PRLR), a landmark-based morphometric study and a cytogenetic analysis. Our data distinguished three main groups in the studied species, corresponding to H. gemonensis and to two monophyletic clades (E and W) within H. viridiflavus. Clades E and W display a significant genetic (about 4% for Cyt-b a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 62 publications
3
73
0
Order By: Relevance
“…Similar integrative taxonomic approach was carried out by Lourenço et al (2015) for amphibians and Mezzasalma et al (2015) for reptiles. As already pointed out by Cardozo et al (2011) and subsequently confirmed in other works, the species of Ololygon (the former Scinax catharinae clade) have NORs in chromosome pair 6, whereas the species of Scinax (the former Scinax ruber clade) generally have this marker in the chromosome pair 11, which also indicates the conservation of this character to cytogenetically differentiate species of both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similar integrative taxonomic approach was carried out by Lourenço et al (2015) for amphibians and Mezzasalma et al (2015) for reptiles. As already pointed out by Cardozo et al (2011) and subsequently confirmed in other works, the species of Ololygon (the former Scinax catharinae clade) have NORs in chromosome pair 6, whereas the species of Scinax (the former Scinax ruber clade) generally have this marker in the chromosome pair 11, which also indicates the conservation of this character to cytogenetically differentiate species of both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similar integrative taxonomic approach was carried out by Lourenço et al (2015) for amphibians and Mezzasalma et al (2015) for reptiles. As already pointed out by Cardozo et al (2011) and subsequently confirmed in other works, the species of Ololygon (the former Scinax catharinae clade) have NORs in chromosome pair 6, whereas the species of Scinax (the former Scinax ruber clade) generally have this marker in the chromosome pair 11, which also indicates the conservation of this character to cytogenetically differentiate species of both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Araujo et al 2005Araujo et al , 2009Froufe et al 2014Froufe et al , 2016a, recent studies have evidenced patterns of population genetic differentiation that could also be explained by the occurrence of this scenario in Italy (e.g. ; Giovannotti et al 2010;Bogdanowicz et al 2015;Mezzasalma et al 2015). In this context, we aim to provide information for the conservation of freshwater mussels in the Italian Peninsula and Croatian Adriatic coast.…”
Section: Introductionmentioning
confidence: 99%